URGENSI PERKEMBANGAN FISIK MOTORIK TERHADAP PERKEMBANGAN EMOSI ANAK USIA DINI - Sintawati Setyaningsih; Ihda A’yunil Khotimah (QURROTI, 2024)
The aim of this research is to determine the urgency of physical motor developmenton children's emotional development. The type of research used is library research,with data collection methods using secondary data, namely by collecting dataindirectly by examining the object in question. The results of this research show thatearly childhood is a stage of human life that is experiencing rapid development in allaspects and this period only occurs once in a lifetime and will not occur duringadolescence until adulthood. Aspects of development that occur at an early ageinclude physical, motoric, cognitive, language, social emotional development andmoral religious values. One important aspect of development is physical motordevelopment. because it can influence emotional development. Motor skills developin line with the maturity of nerves and muscles, which if these motor skills are notstimulated will affect the child's emotional condition.